The Symbolic Meanings and Philosophical Values of Siak Riau Malay Songket Motifs from a Cultural Semiotics Perspective - Ainuddin Ainuddin; Agusti Efi; M. Abdurrozaq (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2026)
Siak Riau Malay Songket Weaving is a cultural heritage of traditional attire that serves as a symbolic medium conveying the moral, religious, and worldview values of the Malay community. Social change and cultural commodification have shifted how the philosophical meanings embedded in songket motifs are understood. Previous studies have mainly focused on aesthetic aspects, weaving techniques, and economic value, while studies employing Barthes’ cultural semiotics to examine the symbolic meanings of songket motifs remain limited. This study aims to analyze the symbolic meanings, philosophical values, and cultural functions of Siak Malay Songket weaving motifs. The research employs a qualitative-descriptive method using Barthes’ cultural semiotic approach. Data were collected through interviews, observation, documentation, and archival studies of Riau Malay culture. The analysis identified the visual forms of the motifs, interpreted their denotative and connotative meanings, and related them to the cultural values of the Siak Malay community. The findings reveal that songket motifs function not only as visual ornaments but also as representations of moral values, life balance, resilience, politeness, and cosmological awareness. Songket motifs also serve as a medium for character education, a regulator of social ethics, and a symbol of the harmonious relationship between humans, nature, and God. This study enriches the field of cultural semiotics and supports the preservation of Siak Malay cultural identity amidst globalization. Tenun Songket Melayu Siak Riau merupakan warisan budaya busana adat yang berfungsi sebagai media simbolik yang memuat nilai moral, religius, dan pandangan hidup masyarakat Melayu. Perubahan sosial dan komodifikasi budaya menyebabkan pergeseran pemahaman terhadap makna filosofis motif songket. Penelitian sebelumnya lebih banyak berfokus pada aspek estetika, teknik kerajinan, dan nilai ekonomi, sedangkan kajian semiotika budaya Barthes terhadap makna simbolik motif songket masih terbatas. Penelitian ini bertujuan menganalisis makna simbolik, nilai filosofis, dan fungsi budaya motif Tenun Songket Melayu Siak. Penelitian ini bersifat kualitatif-deskriptif dengan pendekatan semiotika budaya Barthes. Data diperoleh melalui wawancara, observasi, dokumentasi, dan studi arsip budaya Melayu Riau. Analisis dilakukan dengan mengidentifikasi bentuk visual motif, menafsirkan makna denotatif dan konotatif, serta menghubungkannya dengan nilai budaya Melayu Siak. Hasil penelitian menunjukkan bahwa motif songket tidak hanya berfungsi sebagai ornamen visual, tetapi juga merepresentasikan nilai moral, keseimbangan hidup, ketangguhan, kesantunan, dan kesadaran kosmologis. Motif songket juga berfungsi sebagai media pendidikan karakter, pengatur etika sosial, dan simbol hubungan harmonis antara manusia, alam, dan Tuhan. Penelitian ini memperkaya kajian semiotika budaya serta mendukung pelestarian identitas budaya Melayu Siak di Tengah era globalisasi.